The Effect of Business Strategy and Environmental Disclosure on Firm Value - Amalia, Fitri Prima Nur; Aryati, Titik; Delfina, Cicely (Devotion : Journal of Research and Community Service, 2023)
This study aims to examine the effect of business strategy and environmental disclosure on firm value. Phenomena related to fluctuations in the Composite Stock Price Index are related to calculating company value, researchers have the aim of testing what factors can affect firm value. The business strategy consists of a cost leadership strategy and a differentiation strategy. The secondary data used in this research is the company's Annual Report and data from Bloomberg. The sample used is the sector Basic Materials, Consumer Non-cyclicals, Consumer Cyclicals, and Healthcare, and Energy during 2018-2021, with 164 firm years of data analyzed. Data analysis using multiple linear regression method. This research method uses classical assumption testing consisting of normality, multicollinearity test, heteroscedasticity test and autocorrelation test. This study also tested the coefficient of determination test (R2), F test, T test. The results of the study show that the variable cost leadership strategy and differentiation strategy have a positive effect on firm value. Likewise, the environmental variable disclosure has a positive effect on company value. This research is expected that both companies and investors can consider factors that can increase company value, so that in making decisions can consider these factors.